Parental Maintenance Responsibility in Fulfilling Children’s Nutritional Needs: A Fiqh Analysis of the Free Nutritious Meal Program (MBG) - Muh Zaitun Ardi; Nadyatul Hikmah Shuhufi (Universitas Muhammadiyah Palu, 2026)
The fulfillment of children’s nutritional needs constitutes an essential component of parental maintenance obligations in Islamic law. Such obligations are not limited to providing food in a quantitative sense, but also encompass the quality of nutrition necessary to support children’s physical growth, health, and overall development. In Indonesia, the Free Nutritious Meal Program (MBG) has emerged as a public policy initiative aimed at addressing malnutrition, reducing stunting, and improving the quality of national human resources. The implementation of this program raises normative questions concerning the relationship between parental responsibilities and the role of the state in ensuring children’s nutritional rights. This study examines the position of the MBG program within the framework of Islamic jurisprudence on child maintenance and analyzes its implications for parental obligations. The research employs a normative Islamic legal approach through library research, supported by fiqh analysis, maqasid al-shari‘ah, and public policy perspectives. The findings indicate that parental maintenance obligations remain inherent and are not nullified by the existence of the MBG program. Rather, the program functions as a complementary form of state social support aimed at strengthening the fulfillment of children’s nutritional rights. From the perspective of maqasid al-shari‘ah, the MBG program aligns with the objectives of protecting life (hifz al-nafs), preserving intellect (hifz al-‘aql), and safeguarding future generations (hifz al-nasl), provided that its implementation is conducted fairly, proportionally, and without generating new forms of harm.